2016
DOI: 10.21608/bvmj.2016.31404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some factors on prevalence of FMDV antigen in both cattle and buffaloes in Egypt

Abstract: The present study was carried out for detection and identification of the isolated FMDV from infected tissue samples using serotyping antigen detection ELISA kit (IZSLER ELISA Kit).Thirty six lesion samples were collected from different localities (Menofia, Gharbia, Kalyoubia, Giza and Sharquia governorates) during the period from May 2014 to July 2015.The obtained results indicated that clinically, unvaccinated infected cattle in Gharbia governorate 2014were positive to FMDV infection serotype O. Samples coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…The results of RT-PCR revealed FMD virus serotype O in the examined sample which has been responsible for many recent outbreaks in Egypt as reported by Ibrahim, et al (2014) and also by Aidaros, et al (2016) who found that the most prevalent serotype was (O) in Gharbia and Kaluabiagovernorates during 2014-2015. However, the involvement of other virus strains such as A and SAT2 were previously isolated in Egypt by El-Ashmawy, et al (2013), El-Bayoumy, et al (2014) and Ali, et al (2016).…”
Section: Discussionsupporting
confidence: 55%
“…The results of RT-PCR revealed FMD virus serotype O in the examined sample which has been responsible for many recent outbreaks in Egypt as reported by Ibrahim, et al (2014) and also by Aidaros, et al (2016) who found that the most prevalent serotype was (O) in Gharbia and Kaluabiagovernorates during 2014-2015. However, the involvement of other virus strains such as A and SAT2 were previously isolated in Egypt by El-Ashmawy, et al (2013), El-Bayoumy, et al (2014) and Ali, et al (2016).…”
Section: Discussionsupporting
confidence: 55%